Lighting the Path: Light Delivery Strategies to Activate Photoresponsive Biomaterials In Vivo. (12th September 2021) - Pearson, Samuel; Feng, Jun; del Campo, Aránzazu
Abstract: Photoresponsive biomaterials are experiencing a transition from in vitro models to in vivo demonstrations that point toward clinical translation. Dynamic hydrogels for cell encapsulation, light‐responsive carriers for controlled drug delivery, and nanomaterials containing photosensitizers for photodynamic therapy are relevant examples. Nonetheless, the step to the clinic largely depends on their combination with technologies to bring light into the body. This review highlights the challenge of photoactivation in vivo, and presents strategies for light management that can be adopted for this purpose. The authors' focus is on technologies that are materials‐driven, particularly upconversion nanoparticles that assist in "direct path" light delivery through tissue, and optical waveguides that "clear the path" between external light source and in vivo target. The authors' intention is to assist the photoresponsive biomaterials community transition toward medical technologies by presenting light delivery concepts that can be integrated with the photoresponsive targets. The authors also aim to stimulate further innovation in materials‐based light delivery platforms by highlighting needs and opportunities for in vivo photoactivation of biomaterials. Abstract : The translation of photoresponsive biomaterials to clinical applications hinges on effective light delivery in the body. This review highlights the challenges of in vivo light delivery and the materials‐based light management technologies that can facilitate the photoactivation of biomaterials in the human body, particularly upconversion nanoparticles and optical waveguides.